2009
DOI: 10.1007/s10643-009-0361-9
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Inservice and Preservice Teachers’ Perceived Levels of Preparedness to Handle Stress in their Students

Abstract: This article reports a study that investigated preservice and inservice early childhood teachers' perceived levels of preparedness to handle stress in early childhood and elementary education students. A survey that included vignettes was used to collect data. Data were analyzed both qualitatively and statistically, using one-way ANOVA, t-test, and descriptive statistics. Results showed that, on average, preservice and inservice teachers perceived themselves as moderately prepared to handle stress in their stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 18 publications
2
12
0
2
Order By: Relevance
“…The findings reported here regarding the professional enrichment of teachers through contributions made by university students reinforce the findings of other research, for example, by Stipek and Byler (1997), Carlson and McKennan (2000), Onchwari (2010), Gialamas and Nikolopoulou (2010), Jensen and Shepston (1997), and Cohan and Honigsfeld (2011), among others.…”
Section: Discussionsupporting
confidence: 90%
“…The findings reported here regarding the professional enrichment of teachers through contributions made by university students reinforce the findings of other research, for example, by Stipek and Byler (1997), Carlson and McKennan (2000), Onchwari (2010), Gialamas and Nikolopoulou (2010), Jensen and Shepston (1997), and Cohan and Honigsfeld (2011), among others.…”
Section: Discussionsupporting
confidence: 90%
“…However, training for teachers in this area is not keeping pace with the research (Klassen, Perry, & Frenzel, ). Approximately two‐thirds of teachers perceive themselves as being moderately or poorly prepared for understanding and regulating emotions at work (Onchwari, ). Researchers have found that there are minimal opportunities for training once students leave the university classroom (Foster, Johnson‐Shelton, & Taylor, ), which suggests that preservice training in this area is critical (Palomera et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The influx of dissatisfied teachers has prompted education researchers to examine the teacher attrition phenomenon extensively (e.g. Mahan, 2010;McCann & Johannessen, 2004;Onchwari, 2009). Hong (2010) surmised that "current studies have focused on demographic characteristics of the individual teachers such as gender, age, ethnicity, or marital status, or school characteristics such as average class size, expenditure, poverty enrollment, students demographics and minority enrollment" (pp.…”
Section: Rationale and Background For The Studymentioning
confidence: 99%